Bahasa Batak Di Tengah Arus Globalisasi: Eksplorasi Penyebab Hilangnya Kemampuan Berbahasa Batak Pada Kalangan Pemuda Batak Perkotaan: Batak Language in the Midst of Globalization: An Exploration of the Causes of the Loss of Batak Language Skills among Urban Batak Youth - Daniel Gian Axel Destrarata Pasaribu; Riris Johanna Siagian (MURAI: Jurnal Papua Teologi Konstekstual, 2026)
The Batak language is an essential component of the cultural identity of the Batak people, preserved for generations. However, in the face of increasing globalization, the ability to speak Batak among urban Batak youth has significantly declined. This study aims to explore the causes behind the loss of Batak language proficiency among young Batak people living in urban areas. The primary focus is to identify the factors contributing to the decline in Batak language use, particularly in relation to urbanization, cultural change, and the impact of globalization. Using a qualitative approach, the research investigates the views and experiences of Batak youth in major cities and connects them with ongoing social dynamics. The findings reveal that rapid urbanization and cultural shifts are major factors hindering the younger generation's ability to retain and practice the Batak language. The dominance of the Indonesian language as the national language, along with the widespread use of foreign languages in daily life, further weakens young people's ties to their native language and culture. While there are efforts to preserve the Batak language through cultural and family initiatives, the strong influence of globalization demands adjustments in language practices. Therefore, strategic efforts are needed to address this issue, including more intensive Batak language education and broader cultural preservation initiatives that actively involve the youth.